Long Term Follow-up of Intralesional Laser Photocoagulation for Head and Neck Lymphatic Malformations Using Neodymium-Yttrium-Aluminium-Garnet Laser. Issue 3 (March 2020) - Chang, Cheng-Jen; Hsiao, Yen-Chang
Abstract : Background: Lymphatic malformations remain a challenge for patients and plastic surgeons. Promising results have been reported using intralesional laser photocoagulation (ILP) for treating vascular anomalies. Background Data: The objective of our study is to review the long-term results of a large series of lymphatic malformations in patients treated with ILP. Materials and Methods: A retrospective review of 190 head and neck lymphatic malformations in patients were treated by ILP with an neodymium-yttrium-aluminum-garnet (Nd:YAG) laser (1064 nm) over a period of 20 years (January 1997–January 2016). Patients' ages ranged from 10 months to 12 years and 6 months (mean, 1 year and 11 months). The patient group consisted of 98 female and 92 male patients. Results: Patients were treated with an Nd:YAG laser (Sharplan Inc, Allendale, New Jersey) delivered through a 600-μm optical fiber. Laser power was set at 7 to 15 W and delivered with a pulse duration of 7 to 15 seconds. All patients demonstrated improvement as judged by clinical assessment of the reduction in lesion size (range, 65%–100%; mean reduction, 85%). One hundred fifty-two (80%) patients had a more than 65% reduction of the volume in lymphatic malformations at 3 months after 1 treatment, and 171 (90%) patients had a more than 85% reduction of the volume after 2 treatments. Excellent results were seen in 19 (10%) patients after 3 treatments. Postoperative complications were related to photocoagulation that was delivered too extensively or superficially, with resultant ulceration, infection, induration, and scarring. Conclusions: Throughout the course of our long-term study, ILP using an Nd:YAG laser is an effective treatment modality for lymphatic malformations. Complications can be avoided if the potential for harm is kept in mind.